Periscapular Strength Profile Changes in Collegiate Baseball Pitchers Over the Course of a Season - Patrick S Pabian; Victoria Roach; Roselin Howard; Lauren Johnston; Ryan McGuire (International Journal of Sports Physical Therapy)
# Background